Réponses

Meilleure réponse !
2014-05-08T00:35:43+02:00
E= 7 - 5+ (2 - 3) - (-7 + 5 - 3)
E = 7 - 5 + (-1) - (-5)
E = 7 - 5 -1 + 5
E = 7 + 5 - 5 - 1
E = 12 - 6
E = 6

F= -10 - (5 - 3 + 2) + (- 13 + 12)
F = -10 - (4) + (-1)
F = -10 - 4 - 1
F = - 15

G= 12- ( - 8 +4 - 7) - (9 +3 - 4)
G = 12 - (-11) - ( 8 )
G = 12 + 11 - 8
G = 23 - 8
G = 15

T= 2 - [ 7 - (11 - 23)] - ( - 14 + 8)
T = 2 - [ 7 - ( -12 ) ] - ( - 6 )
T = 2 - ( 7 + 12 ) + 6
T = 2 - ( 19 ) + 6
T = 2 - 19 + 6
T = 2 + 6 - 19
T = 8 - 19
T = - 11